2013
DOI: 10.1088/0952-4746/33/3/693
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impact of a system for real-time visualisation of occupational radiation dose rate during fluoroscopically guided procedures

Abstract: Optimisation of radiological protection for operators working with fluoroscopically guided procedures has to be performed during the procedure, under varying and difficult conditions. The aim of the present study was to evaluate the impact of a system for real-time visualisation of radiation dose rate on optimisation of occupational radiological protection in fluoroscopically guided procedures. Individual radiation dose measurements, using a system for real-time visualisation, were performed in a cardiology la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 32 publications
4
43
2
Order By: Relevance
“…The system consisted of four individual personal dosimeters (PDMs), placed above the lead apron at chest level. The PDMs estimated the user's dose, equivalent to the dose in tissue at a depth of d ¼ 10 mm (Hp(10)) (14). Within the scope of the present study, the PDMs of the two main operators were analyzed.…”
Section: Real-time Occupational Dose Monitoring Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The system consisted of four individual personal dosimeters (PDMs), placed above the lead apron at chest level. The PDMs estimated the user's dose, equivalent to the dose in tissue at a depth of d ¼ 10 mm (Hp(10)) (14). Within the scope of the present study, the PDMs of the two main operators were analyzed.…”
Section: Real-time Occupational Dose Monitoring Systemmentioning
confidence: 99%
“…As a consequence, a proactive approach is now feasible, and the operator can immediately adapt technical settings or adjust use of protective devices (9). Although patient dose monitoring systems and realtime occupational dose monitoring systems proved to be effective in routine clinical situations (11)(12)(13)(14)(15)(16)(17), implications of the combined use of the two systems were not evaluated. The purpose of the present study was to determine the effect on patient radiation exposure of the combined use of a patient dose monitoring system and a real-time occupational dose monitoring system.…”
mentioning
confidence: 99%
“…A method to optimize radiation protection during fluoroscopy is knowledge of radiation dose levels and of basic strategies to minimize these levels . Awareness of dose levels can be provided to specialists using a system that gives real‐time information about the received dose . The Dose Aware system (Philips Healthcare, Best, the Netherlands) contains personal dosimeters for real‐time visualization of the received dose on a monitor.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the system can help to optimize staff members’ radiation protection during fluoroscopy. Recently, the Dose Aware system was used by Sandblom et al . to evaluate its impact on the dose rate of cardiologists during fluoroscopically guided procedures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation